A cobalt complex with a bioinspired molybdopterin-like ligand: a catalyst for hydrogen evolution. Issue 37 (18th July 2016) - Fogeron, Thibault; Porcher, Jean-Philippe; Gomez-Mingot, Maria; Todorova, Tanya K.; Chamoreau, Lise-Marie; Mellot-Draznieks, Caroline; Li, Yun; Fontecave, Marc
Abstract : A cobalt complex using a bioinspired ligand, that mimics the molybdopterin cofactor, displays very good activity for electrochemical proton reduction in terms of turnover frequency, faradic yields and stability. Abstract : Cobalt dithiolene complexes are a new class of H2 -evolving catalysts. Here we describe the preparation, the structure and the catalytic activity of an original cobalt complex using a bioinspired ligand, a quinoxaline–pyran-fused dithiolene derivative (qpdt 2− ) that mimics the molybdopterin cofactor present in the active sites of formate dehydrogenases. This complex displays very good activity for electrochemical proton reduction under weak acid conditions in terms of turnover frequency, faradic yields and stability. Density functional theory calculations show that protonation of a nitrogen atom of the ligand decreases overpotentials by 520 mV and H2 formation proceeds via protonation of an intermediate Co–H hydride, with an adjacent S atom of the dithiolene ligand serving as a proton relay.